1989
DOI: 10.1016/0020-7292(89)90302-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural transmission of group BStreptococcusduring delivery

Abstract: This is a study of group B Streptococcus during labor of 121 patients in whom group B Streptococcus was isolated in the vagina and/or rectum before delivery. The intrapartum vaginal culture was positive in 55.2% of the antepartum carriers (32/58). When the vaginal culture during delivery was positive, the group B Streptococcus was isolated in the amniotic fluid 2 h after the rupture of membranes in 81% of the cases. The newborns of antepartum carriers, when the labor developed naturally, were colonized by grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…These observations were in accordance with a large study from Bengaluru and Maharashtra but were in contrast to the study from Oxfordshire, United Kingdom. 3,5,9 One important association found in the current study was the association of GBS carriage and duration of ruptured membranes for 10 hours or more. The duration reported in earlier studies was between 12 and 18 hours but, in our study, we found statistically significant association with 10 hours or more duration of ruptured membranes and GBS colonization (p-value = 0.002).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…These observations were in accordance with a large study from Bengaluru and Maharashtra but were in contrast to the study from Oxfordshire, United Kingdom. 3,5,9 One important association found in the current study was the association of GBS carriage and duration of ruptured membranes for 10 hours or more. The duration reported in earlier studies was between 12 and 18 hours but, in our study, we found statistically significant association with 10 hours or more duration of ruptured membranes and GBS colonization (p-value = 0.002).…”
Section: Discussionmentioning
confidence: 51%
“…Around 68 of 110 women The strong evidence for the usefulness of the universal screening at 35 to 37 weeks of pregnancy to prevent GBS neonatal infection was mainly drawn from studies conducted in the United States. [2][3][4][5][6][7] However, GBS is present worldwide and the prevalence of GBS carriers varies in relation to the geographical area and/or a number of demographic factors. [8][9][10][11][12][13][14][15] In the present study, the prevalence of anogenital carriage of GBS was 12.15%.…”
Section: Discussionmentioning
confidence: 99%
“…The number of expected episodes of streptococcal sepsis with each strategy was calculated taking into account the following variables: the prevalence of maternal colonisation and of risk factors; the sensitivity and specificity of antenatal group B streptococcus cultures and of risk factors in predicting intrapartum maternal colonisation; the probability of receiving antibiotics during labour; their efficacy in preventing vertical transmission; the probability of vertical transmission; and the probability of sepsis in colonised babies 2–6,9,10,14–18,24,26–64 (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…[87%] mothers, 35 [88%] pediatricians, and 30 [75%] obstetricians). However, only 17 (43%) obstetricians thought physicians should use this type of technique to help them decide the best way to treat their patients, com¬ pared with 73 (88%) mothers and 29 (73%) pediatri¬ cians.…”
Section: Resultsmentioning
confidence: 99%